2017
DOI: 10.21767/2572-5483.100019
|View full text |Cite
|
Sign up to set email alerts
|

Does the Prevalence of Skin Cancer Differ by Metropolitan Status for Males and Females in the United States?

Abstract: Purpose: Skin cancer is a major health concern in the general population, but there are conflicting findings regarding its relationship to where people live. The purpose of this study was to determine whether skin cancer differs by metropolitan status in the general population of U.S. adult males and females aged 18 and older. Methods:This cross sectional analysis used 2015 data from the Behavioral Risk Factor Surveillance System (BRFSS) for males and females aged 18 years and older. Multiple logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Within this data set, the patients residing in the nonmetropolitan group labeled urban area with 20,000 adjacent to a metropolitan area had the highest incidence of melanoma. This is consistent with the findings of Bram et al, 7 who showed that skin cancer incidence (type unspecified) significantly differed by metropolitan status, with more reports among people living in suburban areas (defined as areas with a population of 20,000-50,000) than in urban or rural areas. The Bram et al study classification of "suburban" is equivalent to the group "urban area with 20,000 adjacent to a metropolitan area" in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Within this data set, the patients residing in the nonmetropolitan group labeled urban area with 20,000 adjacent to a metropolitan area had the highest incidence of melanoma. This is consistent with the findings of Bram et al, 7 who showed that skin cancer incidence (type unspecified) significantly differed by metropolitan status, with more reports among people living in suburban areas (defined as areas with a population of 20,000-50,000) than in urban or rural areas. The Bram et al study classification of "suburban" is equivalent to the group "urban area with 20,000 adjacent to a metropolitan area" in this study.…”
Section: Discussionsupporting
confidence: 92%
“…The matching algorithm unit tests the characteristics needed to categorize skin disorders. The process of extracting features from testing pictures is linked with extracting features from previously learned images [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The matching algorithm is designed so that if illnesses are identified, they are categorized, and, ultimately, patients receive an e-prescription; if no diseases are found, the system classifies the skin as healthy.…”
Section: Input Design Data and Optimizationmentioning
confidence: 99%